2021
DOI: 10.1016/j.jamda.2020.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Sedatives and Sedation at the End of Life in Nursing Homes: A Retrospective Multicenter Cohort Study

Abstract: Objectives: There is scarce information about sedation in nursing homes at the end of life. We aimed to assess (1) the use of sedatives generally and "sedatives with continuous effect," based on objective operational criteria, within the last week of life in nursing homes and (2) factors associated with this treatment. Design: Retrospective cohort study, using the nursing homes' medical records. Setting and Participants: Residents who died in 4 German nursing homes from January 2015 to December 2017 and whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Healthcare professionals who do not perceive and label their treatment as ‘sedation’ will not refer to respective guidelines, even if they are aware of them. This may be one of the reasons for deviations from guidelines regarding sedation, which have been reported particularly for the general palliative care setting, for example regarding indications, processes of decision-making and choice of drugs – including the use of opioids for sedation [ 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare professionals who do not perceive and label their treatment as ‘sedation’ will not refer to respective guidelines, even if they are aware of them. This may be one of the reasons for deviations from guidelines regarding sedation, which have been reported particularly for the general palliative care setting, for example regarding indications, processes of decision-making and choice of drugs – including the use of opioids for sedation [ 17 , 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous data indicate that particularly in general palliative care settings, drugs other than the ones recommended in guidelines are used to reduce a patient’s consciousness at the end of life [ 16 , 17 ]. The quantitative part of this mixed-methods study revealed that administration of sedative drugs was never labelled as ‘sedation’ in the documents of the participating nursing homes [ 18 ]. Given these cultural and setting-specific differences, this study aimed to explore the concept of ‘sedative drugs’ and the intentions of German healthcare professionals in general palliative care when administering sedative drugs at the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…The study results must be considered in the context of the following limitations, which have partly been discussed in the previous publication regarding the quantitative phase. 42 To gain a realistic picture of everyday practice, we chose a retrospective design. However, some data have been recorded incompletely, for example, the route of continuous administration (subcutaneous or intravenous) or symptoms.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The study results must be considered in the context of the following limitations, which have partly been discussed in the previous publication regarding the quantitative phase 42 . To gain a realistic picture of everyday practice, we chose a retrospective design.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…32 One example discussed in this month's JAMDA is the use of sedation to relieve severe distress among persons who are dying. 33 A somewhat different issue around individualization involves medications to relieve symptoms and/or increase quality of life. One such category of drugs is recreational agents such as alcohol and marijuana.…”
Section: Need To Better Tailor Prescribing Based On Resident Characteristicsmentioning
confidence: 99%